Multi-parental QTL mapping of resistance to white spot of maize (Zea mays) in southern Brazil and relationship to QTLs of other foliar diseases - Kistner, María Belén; Galiano-Carneiro, Ana Luísa; Kessel, Bettina; Presterl, Thomas; Miedaner, Thomas (Wiley, 2021)
Maize white spot (MWS) is one of the most important foliar diseases in Brazil causing significant yield losses. Breeding genotypes with MWS resistance is the most sustainable alternative for managing such losses; however, their genetic control is poorly understood. Our objectives were to identify genomic regions controlling MWS resistance and to explore the presence of common regions controlling resistance to MWS, grey leaf spot (GLS) and northern corn leaf blight (NCLB). We performed a multi-parental QTL mapping for MWS and GLS resistance with a total of 474 testcrosses and phenotypic data collected in southern Brazil. Six QTLs for MWS resistance on bins 1.03, 1.04, 6.02, 8.05, 1.03, and 10.06 were detected. These findings were compared with previously reported QTLs for NCLB in the same populations, and a common QTL region (bin 8.05) controlling MWS and NCLB resistances was identified. Our findings contribute to a better understanding of MWS resistance by revealing three QTLs (bin 6.02, 1.03, and 10.06), to the best of our knowledge, not yet described in the literature, that are valuable for improving MWS resistance and one promising candidate region for multiple disease resistance.